Report of the Hospital Sub-committee - Horder, Thomas, 1871-1955 (London : Institutional Management Association)
1943-09-11 1943 1940s 15 pages viii. Maids' Cubicles or Bed Rooms. Bed Easy Chair Waste-paper basket Wardrobe built-in with Occasional Chair Individual built-in wash hat cupboard Rug basins or washing Boot cupboard or rack Curtains cubicles with fitments, Chest of drawers, dress- Long mirror in bedroom such as opaline shelf, ing table & mirror or in corridor nearby towel rail, etc. Table Soiled linen receptacle ix. Bath Rooms. Showers as well as baths Stool Pegs on door Heated towel rail Bath mat Bin for rubbish x. Lavatories. Ash-trays. Sanibins preferably of the automatic incinerator type. xi. Kitchenettes (on each floor of sleeping quarters). Gas or electric cooker Gas or electric water Also on each Floor: Cupboard heater A housemaids' cupboard Sink Bin for rubbish Linen room or cupboard China equipment for Sluice room breakfast or tea xii. Laundry Room. Ironing table Washing sinks Tiled floor Electric irons, Wringer Tiles or enamel-painted with pilot lights Cupboard walls and ceiling xiii. Drying Room (to be adjacent to laundry room). Slatted shelves. Lock-up wire cages for individual laundry. xiv. Shampoo Room. Basins and stools. Electric Dryers. xv. Trunk Room, shelves, ventilated and heated. xvi. Cloak Room, with suitable fittings. xvii. Bicycle Sheds, with suitable stands. xviii. Garage Accommodation. xix. Outdoor recreational facilities. Outdoor recreational facilities such as, outdoor games, tennis courts, etc., and a swimming pool, where existing, should be available for all staff. A.V. Huckle & Son, Ltd., Printers, 66 Ramsden Road, Balham, S.W.12. 292/842/2/104